Methylglyoxal-bis-guanylhydrazone inhibits osteopontin expression and differentiation in cultured human monocytes. - Xia Jin; Hua Xu; Michael S McGrath (PLoS ONE, 2018)
Monocyte activation and polarization play essential roles in many chronic inflammatory diseases. An imbalance of M1 and M2 macrophage activation (pro-inflammatory and alternatively activated, respectively) is believed to be a key aspect in the etiology of these diseases, thus a therapeutic approach that regulates macrophage activation could be of broad clinical relevance. Methylglyoxal-bis-guanylhydrazone (MGBG), a regulator of polyamine metabolism, has recently been shown to be concentrated in monocytes and macrophages, and interfere with HIV integration into the DNA of these cells in vitro. RNA expression analysis of monocytes from HIV+ and control donors with or without MGBG treatment revealed the only gene to be consistently down regulated by MGBG to be osteopontin (OPN). The elevated expression of this pro-inflammatory cytokine and monocyte chemoattractant is associated with various chronic inflammatory diseases. We demonstrate that MGBG is a potent inhibitor of secreted OPN (sOPN) in cultured monocytes with 50% inhibition achieved at 0.1 μM of the drug. Furthermore, inhibition of OPN RNA transcription in monocyte cultures occurs at similar concentrations of the drug. During differentiation of monocytes into macrophages in vitro, monocytes express cell surface CD16 and the cells undergo limited DNA synthesis as measured by uptake of BrdU. MGBG inhibited both activities at similar doses to those regulating OPN expression. In addition, monocyte treatment with MGBG inhibited differentiation into both M1 and M2 classes of macrophages at non-toxic doses. The inhibition of differentiation and anti-OPN effects of MGBG were specific for monocytes in that differentiated macrophages were nearly resistant to MGBG activities. Thus MGBG may have potential therapeutic utility in reducing or normalizing OPN levels and regulating monocyte activation in diseases that involve chronic inflammation.